Threshold-like complexation of conjugated polymers with small molecule acceptors in solution within the neighbor-effect model. Issue 6 (22nd January 2016) - Sosorev, Andrey Yu.; Parashchuk, Olga D.; Zapunidi, Sergey A.; Kashtanov, Grigoriy S.; Golovnin, Ilya V.; Kommanaboyina, Srikanth; Perepichka, Igor F.; Paraschuk, Dmitry Yu.
Abstract : A pronounced cooperative effect leading to a sharp growth of charge-transfer complexes (CTCs) in the electronic ground state is observed. Abstract : In some donor–acceptor blends based on conjugated polymers, a pronounced charge-transfer complex (CTC) forms in the electronic ground state. In contrast to small-molecule donor–acceptor blends, the CTC concentration in polymer:acceptor solution can increase with the acceptor content in a threshold-like way. This threshold-like behavior was earlier attributed to the neighbor effect (NE) in the polymer complexation, i.e., next CTCs are preferentially formed near the existing ones; however, the NE origin is unknown. To address the factors affecting the NE, we record the optical absorption data for blends of the most studied conjugated polymers, poly(2-methoxy-5-(2-ethylhexyloxy)-1, 4-phenylenevinylene) (MEH-PPV) and poly(3-hexylthiophene) (P3HT), with electron acceptors of fluorene series, 1, 8-dinitro-9, 10-antraquinone (DNAQ ), and 7, 7, 8, 8-tetracyanoquinodimethane (TCNQ ) in different solvents, and then analyze the data within the NE model. We have found that the NE depends on the polymer and acceptor molecular skeletons and solvent, while it does not depend on the acceptor electron affinity and polymer concentration. We conclude that the NE operates within a single macromolecule and stems from planarization of the polymer chain involved in the CTC with an acceptor molecule; as a result, the probability of further complexation with the next acceptor molecules at the adjacent repeat units increases. The steric and electronic microscopic mechanisms of NE are discussed.